1975
DOI: 10.1068/p040391
|View full text |Cite
|
Sign up to set email alerts
|

Outline Picture Perception by the Songe of Papua

Abstract: The Songe of Papua New Guinea have little or no indigenous pictorial art. Nevertheless, Songe subjects of both sexes of varying ages and degrees of Western contact were able to identify a wide range of outline drawings depicting objects, animals, and human forms. ‘Kinetic’ scenes and outline drawings portraying colour and texture discontinuities presented some difficulty for the Songe, especially for those over forty years old. Informants over forty in general made significantly more errors than those under fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
47
0
1

Year Published

1977
1977
2015
2015

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 100 publications
(48 citation statements)
references
References 9 publications
0
47
0
1
Order By: Relevance
“…Perceptual psychologists, Kennedy and Silver (1974) and Kennedy and Ross (1975) were perhaps the first to emphasize such a correspondence. A number of other investigators have employed perceptual psychology to shed light on the graphic strategies utilized in palaeoart, most notably Halverson (1992aHalverson ( , 1992b, Deręgowski (1989Deręgowski ( , 1995, and Hudson (1998).…”
Section: Evolutionary Constraints and The Visual Brainmentioning
confidence: 94%
“…Perceptual psychologists, Kennedy and Silver (1974) and Kennedy and Ross (1975) were perhaps the first to emphasize such a correspondence. A number of other investigators have employed perceptual psychology to shed light on the graphic strategies utilized in palaeoart, most notably Halverson (1992aHalverson ( , 1992b, Deręgowski (1989Deręgowski ( , 1995, and Hudson (1998).…”
Section: Evolutionary Constraints and The Visual Brainmentioning
confidence: 94%
“…Winter (1963) and Duncan, Gourlay, and Hudson (1973) found lines for motion, collision, and Downloaded by [The University Of Melbourne Libraries] at 10:53 20 June 2016 pain to be understood much later than lines depicting objects (see discussion by Kennedy, 1977). Kennedy and Ross (1975) found that the PapuandNew Guineans who had understood outlines depicting edges of objects did not recognize lines representing movement.…”
mentioning
confidence: 94%
“…These "surface layout" features (Gibson, 1966) seem to be universal in depictions-they appear wherever cave or rock-face drawings are found (Kennedy & Silvers, 1974). Outline drawings showing these features were recognized by PapuandNew Guineans who had had no training with outline drawings (Kennedy & Ross, 1975).…”
mentioning
confidence: 97%
“…The clearest experiment, because solely concerned with the recognition of outline depictions, is that of Kennedy and Ross (1975) with the Songe of New Guinea, where they found an extremely high rate of immediate recognition of familiar objects, and most of the subjects who responded incorrectly the first time were, as soon as they were told what the figures represented, quickly able to identify details of the depictions, showing that they did recognize the figures. Deregowski et a1 (1972;cf Deregowski 1976), on the other hand, found with their subjects, the Me'en of Ethiopia, that although they responded well after the pictures had been printed on familiar material, they were in some cases very slow and in need of coaching.…”
Section: Recognition Of Line Drawingsmentioning
confidence: 99%